Efficacy of traditional Chinese medicine versus angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and their combinations in the treatment of IgA nephropathy: a systematic review and network meta-analysis - Ma, Sijia; Jiang, Yuhua; Qian, Linlin; Wang, Meng; Xu, Shijie; Wang, Guowei (Frontiers in Pharmacology, 2024)
Background: IgA nephropathy (IgAN), a condition posing a significant threat to public health, currently lacks a specific treatment protocol. Research has underscored the potential benefits of traditional Chinese medicine (TCM) for treating IgAN. Nevertheless, the effectiveness of various intervention strategies, such as combining TCM with angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs), lacks a comprehensive systematic comparison. Therefore, this study aimed to conduct a network meta-analysis to assess the clinical efficacy of ACEIs, ARBs, TCM, and their combinations in treating IgAN to offer novel insights and approaches for the clinical management of IgAN.Methods: A systematic review conducted until November 2023 included relevant literature from databases such as PubMed, Embase, Cochrane, Web of Science, Scopus, CNKI, and Wanfang. Two independent researchers screened and assessed the data for quality. Network and traditional metaanalyses were performed using Stata 18.0 and RevMan 5.3 software, respectively. Outcome measures included 24-hour urinary protein quantification (24 hpro), estimated glomerular filtration rate (eGFR), serum creatinine (Scr), blood urea nitrogen (BUN), and adverse event incidence rates (ADRs). Forest plots, cumulative ranking probability curves (SUCRA), and funnel plots generated using Stata 18.0 facilitated a comprehensive analysis of intervention strategies' efficacy and safety.Results: This study included 72 randomized controlled trials, seven interventions, and 7030 patients. Comparative analysis revealed that ACEI + TCM, ARB + TCM combination therapy, and TCM monotherapy significantly reduced the levels of 24 hpro, eGFR, Scr, and BUN compared to other treatment modalities (P < 0.05). TCM monotherapy demonstrated the most favorable efficacy in reducing eGFR levels, whereas the combination of ARB + TCM reduced Scr, 24 hpro, and BUN levels, suggesting that ARB + TCM may represent the optimal intervention strategy. No statistically significant differences were observed among the various treatment strategies in terms of ADR (P > 0.05).The combination of ACEI or ARB with TCM demonstrated superior efficacy compared to ACEI/ARB monotherapy in the treatment of IgAN without any significant ADRs. Therefore, combination therapies can be used to enhance therapeutic outcomes based on individual patient circumstances, highlighting the use of TCM as a widely applicable approach in clinical practice.